Predictive coding of multisensory timing. (April 2016) - Shi, Zhuanghua; Burr, David
Highlights: We review duration-related temporal phenomena and related computational models. Those temporal phenomena can be explained within the predictive coding framework. Subjective time is an outcome of integration process of likelihood and prior. Prediction error calibrates internal temporal prior in Bayesian manner. Abstract : The sense of time is foundational for perception and action, yet it frequently departs significantly from physical time. In the paper we review recent progress on temporal contextual effects, multisensory temporal integration, temporal recalibration, and related computational models. We suggest that subjective time arises from minimizing prediction errors and adaptive recalibration, which can be unified in the framework of predictive coding, a framework rooted in Helmholtz's 'perception as inference'.